A review of the Caligus productus species group, with the description of a new species, new synonymies and supplementary descriptions - Boxshall, Geoff A; El-Rashidy, Hoda H. (Zootaxa, 2009)
The productus-group within the sea lice genus Caligus Müller, 1785 is characterised by the loss of two and the reduction or loss of the third of the three plumose setae normally carried on the posterior margin of the distal exopodal segment of the first swimming leg. We describe a new species, Caligus lethrinicola n.sp., from a lethrinid host collected in New Caledonia. We review the group and recognize 15 species as valid, including the new species. The type material of the three varieties of Caligus mauritanicus Brian, 1924 is re-examined and the var. temnodontis is here recognized as a distinct species, Caligus temnodontis Brian, 1924. The typical and miniscula varieties are recognised as synonyms of Caligus dakari van Beneden, 1892 and C. haemulonis Krøyer, 1863 respectively. Additional synonymies are proposed within the group. Supplementary observations are presented on the morphology of C. dakari, C. haemulonis and C. temnodontis. A brief differential diagnosis is presented for each of the 14 previously described valid species and a key to species has been constructed.